Development of a representational conceptual evaluation in the first law of thermodynamics. (August 2016) - Sriyansyah, S P; Suhandi, A
Abstract: As part of an ongoing research to investigate student consistency in understanding the first law of thermodynamics, a representational conceptual evaluation (RCET) has been developed to assess student conceptual understanding, representational consistency, and scientific consistency in the introductory physics course. Previous physics education research findings were used to develop the test. RCET items were 30 items which designed as an isomorphic multiple-choice test with three different representations concerning the concept of work, heat, first law of thermodynamics, and its application in the thermodynamic processes. Here, we present preliminary measures of the validity and reliability of the instrument, including the classical test statistics. This instrument can be used to measure the intended concept in the first law of thermodynamics and it will give the consistent results with the ability to differentiate well between high-achieving students and low-achieving students and also students at different level. As well as measuring the effectiveness of the learning process in the concept of the first law of thermodynamics.